Pocket glossary for commonly used research terms - Holosko, Michael J.; Thyer, Bruce A. (Thousand Oaks, Calif. : SAGE Publications, 2011)
'This book contains over 1500 research and statistical terms, written in jargon-free, easy-to-understand terminology to help students understand difficult concepts in their research courses. This pocket guide is in an ideal supplement to the many discipline-specific texts on research methods and statistics.'--pub. desc.
Includes bibliographical references.
Keywords: Social sciences -- Research -- Terminology -- Handbooks, manuals, etc; Research -- Terminology -- Handbooks, manuals, etc